The Influence of Management Control Systems and Innovation Capabilities on Business Performance (A Study at PT Menara Mas Futures) - Filosovi Marti Sania; NR Ayke Nuraliati; Julfan Herliansyah (CV Edujavare Publishing, 2026)
The increasingly dynamic, complex, and competitive business environment requires companies to manage resources effectively and develop sustainable competitive advantages. In the financial services industry, particularly futures brokerage firms, business performance is influenced not only by financial outcomes but also by the effectiveness of management control systems and the organization’s innovation capabilities. PT Menara Mas Futures faces challenges related to operational risks, regulatory compliance, service quality, and customer trust, making these factors essential for maintaining business performance. This study aims to analyze the influence of Management Control Systems and Innovation Capability on Business Performance at PT Menara Mas Futures. A quantitative research method with descriptive and verificative approaches was employed. Primary data were collected through questionnaires distributed to 33 employees selected using probability sampling techniques. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings indicate that Management Control Systems have a positive and significant effect on Business Performance, with a path coefficient of 0.995, a t-statistic of 24.408, and a p-value of 0.000. Conversely, Innovation Capability has a negative and significant effect on Business Performance, with a path coefficient of -0.164, a t-statistic of 3.000, and a p-value of 0.003. The R-Square value of 0.930 demonstrates that both variables explain 93% of the variance in Business Performance. The study concludes that Management Control Systems are the primary driver of business performance, while innovation initiatives should be implemented cautiously and aligned with regulatory requirements.